Reliability of load-cell dynamometry hamstring, hip adductor and hip abductor strength testing in elite youth soccer players - Adams, S.; Drew, M.; Wollin, M.; Smith, C.; Renwick, N.; Johnson, B.; Schultz, A. (The Journal of Strength and Conditioning Research, 2021)
Reduced muscle strength in sports like soccer may negatively impact sports performance and also predispose an athlete to sustaining a muscle strain injury. The hamstrings and hip adductors are sensitive to soccer induced fatigue, demonstrated by reduced eccentric, concentric and isometric strength up to 72-hours post-match. A valid and reliable series of dynamometry-based strength tests that can be integrated safely and efficiently within the training environment may assist sports medicine staff in the decision making process around soccer induced fatigue and return to play procedures. Purpose: To determine inter and intra-tester reliability as well as minimal detectable change (MDC) and SEM for knee flexion, hip adductor and hip abductor strength as measured by load-cell dynamometry in an elite youth soccer setting. Methods: 22 uninjured elite-level youth male soccer players (age 18.0 ± 1.3 years, height 179.2 ± 6.6 cm, weight 72.1 ± 7.6 kg, BMI 22.4 ± 1.8) were recruited from the Newcastle Jets youth soccer team. Unilateral maximal isometric peak hamstring, hip adductor and hip abductor strength was evaluated by externally fixed dynamometry for intra-tester, inter-week and inter-tester, intra-day reliability. To enable this, consecutive pairwise intra class correlation coefficients (ICC3, 1) with corresponding 95% confidence intervals (95% CI) were utilised. The hamstring test protocol was replicated as per previous research to correlate with the terminal swing phase of the running gait cycle. The hip adductor and abductor testing protocols were formulated according to the teams' needs, with an aim to assess their reliability. Results: The reliability of the hamstring, hip adductor and hip abductor strength results are presented in Table 1. The hip abductor protocol proved to be the most reliable of all muscle groups tested, able to detect strength changes of approximately 11-18% (MDC %). The hip adductor protocol demonstrated the lowest absolute reliability of the tests (MDC = 22-32%). The hamstring protocol demonstrated high levels of inter-week, intra-tester (0.94 ICC) and intra-day, inter-tester (0.95 ICC) reliability and was able to detect strength changes of approximately 18-24% (MDC %). Conclusions: Load-cell dynamometry displays good to high levels of reliability in elite youth male soccer players for hamstring, hip adductor and hip abductor strength testing. Practical Application: Load-cell dynamometry as described in this research is cost-effective, safe and easy to implement, and may be used by sports medicine and strength and conditioning support staff to help inform decision making about player's strength-status throughout the playing-season and may also help identify potential injury risks.